2006
DOI: 10.1111/j.1440-1746.2005.04112.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DQB1 locus and gastric cancer in Helicobacter pylori infection

Abstract: Background and Aims: It has been suggested that the incidence of digestive diseases associated with Helicobacter pylori is influenced by the strain diversity of H. pylori, factors involving the host or environment, and the duration of infection. The authors have previously reported that human leukocyte antigen (HLA)-DQB1*0401 plays an important role in the development of atrophic gastritis in H. pylori infected patients. The aim of the present study was to investigate the relationship between HLA-DQB1 genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…We did not find a positive association with DRB1*0405 in diffuse‐type GC. Our findings essentially agree with Watanabe et al ,14 in which the allele frequency of DQB1*0401 is higher in patients with intestinal‐type GC when compared with age‐ and sex‐matched H. pylori ‐infected NUD controls (19/36 = 52.8% vs . 15/49 = 30.6%, p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…We did not find a positive association with DRB1*0405 in diffuse‐type GC. Our findings essentially agree with Watanabe et al ,14 in which the allele frequency of DQB1*0401 is higher in patients with intestinal‐type GC when compared with age‐ and sex‐matched H. pylori ‐infected NUD controls (19/36 = 52.8% vs . 15/49 = 30.6%, p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies related to HLA antigens in the literature have focused on screening of class II antigens especially in cancer cases (12,14) . Our study was the (10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported associations of HLA alleles with malignant tumors caused by microbe infections (Li et al ., 2005; Watanabe et al ., 2006; Wu et al ., 2006). Human tumour cells express diverse types of antigens, depending on the aetiology and pathogenesis of the disease (Jager et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%